Connecting the dots: Nonlinear patterns in the presence of symbolic and nonsymbolic numerical standards - Roland Imhoff; Paul Barker (Judgment and Decision Making, 2023)
Much like other social and nonsocial evaluations, estimates of numerical quantities are susceptible to comparative influences. However, numerical representations can take either a nonsymbolic (e.g., a grouping of dots) or a symbolic numerical form (e.g., Hindu–Arabic numerals), which each produce comparative biases in opposite directions. The current work takes a fine-grained curve fitting approach across a wide range of values to the investigation of their potential nonlinear influence in the context of a numerical estimation task. A series of 3 experiments (N = 1,613) showed how nonsymbolic standards produce linear contrastive patterns (Study 1), whereas symbolic numerical anchors show a cubic assimilative effect with a leveling off in strength for more extreme standards (Study 2). Sequential contrast from the previous patterns and assimilation to the previous response were found to be present and additive in the presence of both representations but were larger in absence of the symbolic numerical anchors (Study 3).